Multiscale simulations suggest a mechanism for integrin inside-out activation. - Kalli, A; Campbell, I; Sansom, MS (2011)
Integrins are large cell-surface adhesion receptors that can be activated to a high affinity state by the formation of an intracellular complex between the integrin β-subunit tail, the membrane, and talin. The F2 and F3 subdomains of the talin head play a key role in formation of this complex. Here, activation of the integrin αIIb/β3 dimer by the talin head domain was probed using multiscale molecular dynamics simulations. A number of novel insights emerge from these studies, including (i) the importance of the integrin αIIb subunit F992 and F993 residues in stabilizing the "off" state of the αIIb/β3 dimer, (ii) a crucial role for negatively charged groups in the F2-F3/membrane interaction, (iii) binding of the talin F2-F3 domain to negatively charged lipid headgroups in the membrane induces a reorientation of the β transmembrane (TM) domain, (iv) an increase in the tilt angle of the β TM domain relative to the bilayer normal helps to destabilize the α/β TM interaction and promote a scissor-like movement of the integrin TM helices. These results, combined with various published experimental observations, suggest a model for the mechanism of inside-out activation of integrins by talin.